2020
DOI: 10.1002/adma.202004111
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite‐Derivative Valleytronics

Abstract: Halide perovskites are revolutionizing the renewable energy sector owing to their high photovoltaic efficiency, low manufacturing cost, and flexibility. Their remarkable mobility and long carrier lifetime are also valuable for information technology, but fundamental challenges like poor stability under an electric field prevent realistic applications of halide perovskites in electronics. Here, it is discovered that valleytronics is a promising route to leverage the advantages of halide perovskites and derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…The two aromatic rings are joined together by pyrazine rings that are made up of a six-membered D 2h point group with two N atoms facing each other. 41 The optimized lattice constants of the unit cell are 8.60 Å and 8.33 Å for the individual Cs 3 Bi 2 I 9 and C 2 N, respectively, which are consistent with the previously reported results, 40,69 confirming the reliability of the following calculated results. The analogous lattice constants of Cs 3 Bi 2 I 9 and C 2 N suggest the likelihood of epitaxial stacking, especially in few-layer systems.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The two aromatic rings are joined together by pyrazine rings that are made up of a six-membered D 2h point group with two N atoms facing each other. 41 The optimized lattice constants of the unit cell are 8.60 Å and 8.33 Å for the individual Cs 3 Bi 2 I 9 and C 2 N, respectively, which are consistent with the previously reported results, 40,69 confirming the reliability of the following calculated results. The analogous lattice constants of Cs 3 Bi 2 I 9 and C 2 N suggest the likelihood of epitaxial stacking, especially in few-layer systems.…”
Section: Resultssupporting
confidence: 90%
“…These values are in good agreement with the previous theoretical calculations. 29,44,50,69 Moreover, in Fig. 1(e) and (f), the calculated total density of states (TDOS) and the projected density of states (PDOS) show that the CBM of the Cs 3 Bi 2 I 9 comprises I-5p and Bi-6p states, while the VBM is only dominated by I-5p states.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, nontoxic, all-inorganic, lead-free Bi-based perovskites have attracted significant attention owing to their stability, high photoluminescence, high quantum yield, and tunable bandgaps [11][12][13][14][15][16][17]. They have been widely used in applications, such as memory devices, photodetectors, solar cells, and X-ray detectors [18][19][20][21][22][23][24][25][26]. However, many studies have shown that there are some challenges to overcome for the use of Cs 3 Bi 2 X 9 (X = I, Br, and Cl) perovskites in photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we will finish by demonstrating how the retrospective analysis using ToF-SIMS can be very powerful and useful for exploring any single feature in 2D materials [3,4]. Typically, ToF-SIMS acquisition is recording a full mass range spectrum per pixel (or voxel), which permits to isolate and to decorrelate specific regions of interest for resolving interfaces, diffusion, and doping in thin 2D structures.…”
mentioning
confidence: 99%